2021
DOI: 10.3390/vetsci8090179
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Challenges of Jatropha Meal as Novel Biofeed for Animal Production

Abstract: Jatropha curcas L. has gained importance as a source of seed oil for biodiesel production. The meal contained about 60% protein with a good balance of essential amino acids, containing various bioactive compounds, including saponins, phytic acids, trypsin inhibitors, lectins, phenolics, and flavonoids, which render it as a potential biofeed for animal production. The Jatropha meal demonstrated various biological activities, including antioxidant, antibacterial, and anti-inflammatory effects which enhance its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 97 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…These signals belong to fatty acids and aromatics ( Figure 1 c). Oskoueian et al [ 30 ] report the presence of carboxyl, hydroxyl, methyl groups, fixed anionic, and cationic traces with antimicrobial, anti-inflammatory, and antioxidant activities in J. curcas flour.…”
Section: Resultsmentioning
confidence: 99%
“…These signals belong to fatty acids and aromatics ( Figure 1 c). Oskoueian et al [ 30 ] report the presence of carboxyl, hydroxyl, methyl groups, fixed anionic, and cationic traces with antimicrobial, anti-inflammatory, and antioxidant activities in J. curcas flour.…”
Section: Resultsmentioning
confidence: 99%
“…According to Makkar and Becker [18], JSC has trypsin inhibitory activity similar to that of soybean meal and is found in all parts of the kernel [29]. Trypsin inhibitors have been linked to pancreatic hypertrophy and hyperplasia [30], disrupting the digestive processes in monogastric animals and consequently stunting growth [8,31]. Ruminants are less sensitive to plant bioactive compounds than monogastric animals because rumen bacteria can greatly break down lectins, phytate, and trypsin inhibitors [31].…”
Section: Trypsin Inhibitorsmentioning
confidence: 99%
“…As a defense mechanism against viruses, pests, and predators, saponins execute their principal biological effects through contact with membrane components. Characterized by their hemolytic activity and foaming properties, saponins influence the permeability of the small cells of the intestinal mucosa, thereby affecting the transport of active nutrients [31,32,39]. Since Jatropha saponins are non-hemolytic and are present in both poisonous and non-toxic forms of the plant at comparable concentrations, authors have suggested that they are relatively innocuous [31,40].…”
Section: Saponinsmentioning
confidence: 99%